OPPORTUNITIES FOR THE DEVELOPMENT OF PUBLIC PRIVATE PARTNERSHIP IN THE REGION - Ataniyazova Maksuda Baltabayevna (Scholar Express Journals, 2023)
The use of the mechanism of public-private partnership in the socio-economic system of the region is considered an important direction of economic development. Therefore, public-private partnerships are an important way of ensuring the socio-economic development of the country and an important source of attracting financial resources to investment projects that are under the control of state authorities and cooperate with investors. Based on the relevance of this issue, the article analyzes the possibilities of public-private partnership development in the region and develops relevant proposals and recommendations.
Keywords: public-private partnership; investment; project